Anti-Candidal Activity and In Vitro Cytotoxicity Assessment of Graphene Nanoplatelets Decorated with Zinc Oxide Nanorods - Graziella Ficociello; Maria Giovanna De Caris; Giusy Trillò; Domenico Cavallini; Maria Sabrina Sarto; Daniela Uccelletti; Patrizia Mancini (Nanomaterials, 2018)
Candida albicans is the most common pathogenic fungus that is isolated in nosocomial infections in medically and immune-compromised patients. The ability of C. albicans to convert its form from yeast to hyphal morphology contributes to biofilm development that effectively shelters Candida against the action of antifungals molecules. In the last years, nanocomposites are the most promising solutions against drug-resistant microorganisms. The aim of this study was to investigate the antifungal activity of graphene nanoplateles decorated with zinc oxide nanorods (ZNGs) against the human pathogen Candida albicans. We observed that ZNGs were able to induce a significant mortality in fungal cells, as well as to affect the main virulence factors of this fungus or rather the hyphal development and biofilm formation. Reactive Oxygen Species (ROS) formation in yeast cells resulted one of the mechanisms of ZNGs to induce mortality. Finally, the toxicity of this nanomaterial was tested also on human keratinocyte cell line HaCaT. Our data indicated that ZNGs resulted not toxic when their aggregation state decreased by adding glycerol as emulsifier to ZNGs suspensions or when HaCaT cells were grown on ZNGs-coated glasses. Overall, the results that were obtained indicated that ZNGs could be exploited as an antifungal nanomaterial with a high degree of biocompatibility on human cells.